Assessment and Treatment of Pain in Hospitalized Children at a Tertiary Children's Hospital: A Cross-Sectional Mixed Methods Survey - Nadia Roessler De Angulo; Andrea C. Postier; Lisa Purser; Lena Ngo; Karen Sun; Stefan Friedrichsdorf (MDPI AG, 2024)
(1) Background: Acute pain in hospitalized children remains under-recognized and under-treated. Our objective is to benchmark pain assessment, documentation, treatment, and patient experience in children admitted to a US children's hospital. (2) Methods: A cross-sectional, mixed-method survey of pain for children hospitalized ≥24 h. Charts were reviewed for modalities of pain assessment and treatment for all inpatients. If pain was documented, patients/caregivers were surveyed regarding their experience with pain and its management. (3) Results: Chart review: All 107 patients had ≥1 pain score documented. A total of 47 patients had a pain score ≥0, 35 (74.5%) of whom had ≥1 moderate-severe score. Seventy (65.4%) patients received ≥1 intervention for pain, including medications from ≥1 class (e.g., opioids) (n = 55, 51.4%) and/or integrative/non-pharmacologic intervention(s) (n = 39, 36.4%). There were assessment and documentation gaps. Patient survey: A total of 39 (83.0%) interviews were attempted; 25 (53.2%) were completed. The worst pain was mostly caused by acute illness (n = 13, 52%) and painful procedures (n = 10, 40%). Suggestions for improvement included increasing the use of integrative modalities and optimizing patient-clinician communication. (4) Conclusions: All patients admitted ≥24 h had ≥1 pain score documented; however, gaps in documentation were common. Multimodal treatment and integrative modalities were underutilized. Procedures were a frequent cause of under-treated pain, prompting an institution-wide quality improvement project.